2020
DOI: 10.4285/atw2020.po-1162
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immune monitoring for prediction of cytomegalovirus and BK viral reactivation after kidney transplantation

Abstract: Background: The reactivation of cytomegalovirus (CMV) and BK virus after kidney transplantation is a critical factor that affects donor and graft survival. However, accurate methods for viral reactivation prediction and overall immune status assessment after transplantation remain unavailable. This study aimed to evaluate cellular immunity assays based on the potential for predicting CMV and BK viral reactivation in kidney transplant patients. Methods: Fourteen male and twelve female patients who underwent kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Pretransplant CMV-CMI has been suggested as a risk for posttransplant CMV replication. [2][3][4]17,[21][22][23][24] We selected 44 HLA alleles to analyze the CMV-ELI-SPOT results based on HLA allele frequencies. The frequencies of these 44 HLA alleles in our study were comparable to those found in previous reports (Table S2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pretransplant CMV-CMI has been suggested as a risk for posttransplant CMV replication. [2][3][4]17,[21][22][23][24] We selected 44 HLA alleles to analyze the CMV-ELI-SPOT results based on HLA allele frequencies. The frequencies of these 44 HLA alleles in our study were comparable to those found in previous reports (Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…This requires special attention in identifying risk factors associated with CMV reactivation. Pretransplant CMV‐CMI has been suggested as a risk for posttransplant CMV replication 2–4,17,21–24 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations